A Novel method to represent Access Tree structure by Context Free Grammar with and-or graph in Key Policy based Attribute based Encryption - Senthil Kumar, K.; Malathi, D. (International Journal of Engineering and Technology, 2018)
Important and sensitivity data of users in a third party managed internet or cloud always pose various security as well as privacy issues. Attribute-based encryption (ABE) is a pleasant trend in the literature which addresses above problem in an efficient way, and provides data security and fine-grained access control in a decentralized manner,. Key-policy attribute-based encryption (KP-ABE) is an important type of ABE, in which user can decrypt his message with a set of attributes and private keys are embedded with a access control structure which defines which cipher textÂ  an user can be allowed to decrypt. In this paper we use a probabilistic context free grammar with an And-Or structure to represent access control structure. And-Or graph has high expressive power hence access control structure can be represented in an efficient manner.Â Â